INVESTMENT BASIS AND DEVELOPMENT TRENDS OF SMALL BUSINESS AND ENTREPRENEURSHIP IN UZBEKISTAN - Oblomuradov, Naim (Current Research Journal of History, 2021)
The article describes the investment basis, historical factors and development trends in the development of small business and entrepreneurship in the years of independence of Uzbekistan. It describes the state policy to increase the attractiveness of the investment climate, important factors, conditions and some problems in attracting foreign investment. The article notes that the integration of the industry into the world economic system has allowed Uzbekistan to improve the domestic socio-economic environment, ways to actively attract investment and use it wisely by further encouraging entrepreneurs.